2022
DOI: 10.3390/foods11050696
|View full text |Cite
|
Sign up to set email alerts
|

Drying Behavior and Curcuminoids Changes in Turmeric Slices during Drying under Simulated Solar Radiation as Influenced by Different Transparent Cover Materials

Abstract: Dried turmeric is used as a spice and traditional medicine. The common drying methods for turmeric (Curcuma longa L.) are sun drying and solar drying. In this study, turmeric slices with a thickness of 2 mm were dried at 40, 50, 60, and 70 °C in a laboratory hot-air dryer with a simulated solar radiation applied through transparent polycarbonate cover (UV impermeable) and PMMA cover (UV permeable). Air velocity and relative humidity of drying air were fixed at 1.0 M·s−1 and 25 g H2O kg−1 dry air, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Lee et al [34] reported that light induced the decomposition of yellow turmeric pigment. A similar observation of light-induced decomposition of curcumin was also reported by Komonsingh et al [35]. The above authors have also stated that both direct and indirect solar radiation can decompose the curcumin pigment.…”
Section: Effect Of Processing Conditions On Curcumin Contentsupporting
confidence: 84%
“…Lee et al [34] reported that light induced the decomposition of yellow turmeric pigment. A similar observation of light-induced decomposition of curcumin was also reported by Komonsingh et al [35]. The above authors have also stated that both direct and indirect solar radiation can decompose the curcumin pigment.…”
Section: Effect Of Processing Conditions On Curcumin Contentsupporting
confidence: 84%
“…The results showed that the dried products possessed intensive orange color. Additionally, curcumin, demethoxycurcumin, and total curcuminoids were influenced, where the lowest curcumin content was detected at 40 °C under PMMA 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Thin-layer drying (TLD) is a process in which materials are uniformly distributed within a dryer to generate a thin-layer structure (Akpinar, 2006;Erbay & Icier, 2010). The pace of drying is affected by factors such as the thickness and size of TLD materials (Komonsing, Reyer, Khuwijitjaru, Mahayothee, & Müller, 2022). The cost-effective drying process must be designed using operational mathematical models that optimize various drying parameters.…”
Section: Introductionmentioning
confidence: 99%